Inovasi Layanan Manajemen Haji dan Umroh : Memanfaatkan Media Sosial untuk Edukasi dan Informasi Jamaah - Muhammad Nauval Hazieq; Wardatul Hamro; Abdul Hafiz (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
Innovation in Hajj and Umrah management through the use of social media holds significant potential to enhance service efficiency and quality. Social media platforms like Facebook, Instagram, Twitter, and WhatsApp can be used to quickly and accurately provide education and information to pilgrims. Organizers can deliver guidelines, health tips, and real-time updates about conditions in the holy land, and respond to pilgrims' questions and complaints more efficiently. This research explores how social media can be integrated into Hajj and Umrah management to improve service quality and risk management, focusing on the role of social media in education, responsiveness, and risk management. The findings indicate that social media is effective in disseminating information and enhancing interaction between organizers and pilgrims, though challenges exist in technology access gaps and the risk of spreading inaccurate information.